Вплив похибки зубчастого профілю роторів планетарного гідромотора на його технічний стан - Панченко, Анатолій Іванович; Panchenko, Anatolii; Волошина, Анжела Анатоліївна; Voloshyna, Anzhela; Панченко, Ігор Анатолійович; Panchenko, Ihor; Холод, Ігор Михайлович; Kholod, Ihor; Волошин, А. А. (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У сучасних мехатронних системах приводу активних робочих органів мобільної техніки дедалі частіше знаходять застосування гідромашини об’ємного принципу дії, а саме планетарні гідромотори, які є досить складним механізмом з деталями, що становлять прецизійне з’єднання. Тому однією з проблем, що зумовлюють працездатність планетарних гідромашин, є контроль точності виготовлення його роторів. У результаті проведених досліджень розроблено та обґрунтовано розмірний ланцюг, розроблено розрахункову схему, створено методи та пристрої контролю, встановлено вплив зазору на технічний стан планетарного гідромотора. Установлено, що граничні значення цього проміжку можуть бути використані для нормування функціональних параметрів, що впливають на працездатність гідромотора. /// EN: In modern mechatronic systems of drive of active working bodies of self-propelled machinery, hydraulic machines of the positive displacement principle are increasingly used, namely planetary hydraulic motors, which are a rather complex mechanism with parts that represent a precision connection. Therefore, one of the problems determining the operability of planetary hydraulic machines is the control of the manufacturing accuracy of their rotors. As a result of the conducted research, a dimensional chain was developed that accurately describes the interaction of the toothed profiles of the rotors of the planetary hydraulic motor; a calculation scheme was developed that allows establishing the geometric and functional relationship between the location of the contact points of the toothed profiles of the outer and inner rotors of the planetary hydraulic motor; effective methods and devices for monitoring the manufacturing error of the inner and outer rotors of the planetary hydraulic motor were developed and tested; it was determined that the gap between the rotors (0.02...0.214 mm) is an important parameter characterizing the technical condition of the planetary hydraulic motor; It has been established that the maximum clearance values can be used to standardize the functional parameters that affect the performance of the hydraulic motor, which makes it possible to use the clearance to diagnose the technical condition of hydraulic motors.
The influence of the error of the toothed profile of the rotors of a planetary hydraulic motor on its technical condition
Keywords: система переміщень; методи та засоби контролю; розмірний ланцюг; відхилення форми; displacement system; methods and means of control; dimensional chain; form deviations